2008
DOI: 10.1080/01431160802036516
|View full text |Cite
|
Sign up to set email alerts
|

Thermal remote sensing in the framework of the SEN2FLEX project: field measurements, airborne data and applications

Abstract: A description of thermal radiometric field measurements carried out in the framework of the European project SENtinel-2 and Fluorescence Experiment (SEN2FLEX) is presented. The field campaign was developed in the region of Barrax (Spain) during June and July 2005. The purpose of the thermal measurements was to retrieve biogeophysical parameters such as land surface emissivity (LSE) and temperature (LST) to validate airborne-based methodologies and to characterize different surfaces. Thermal measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 16 publications
2
37
0
1
Order By: Relevance
“…Sobrino et al, 2008;Su et al, 2008;Timmermans, 2008b, c), the knowledge of bio-geophysical parameter retrieval from multi-parameter optical, thermal and microwave data and the ability of direct modeling of the underlying physical processes in forests and grassland remain challenging due to lack of appropriate observation data in humid climate. In EAGLE2006 an intensive filed campaign was conducted using different airborne instruments -an optical imaging sensor, an imaging microwave radiometer, and a flux airplane -for data acquisition and to collect extensive ground measurements simultaneously over one grassland site and two forest sites in addition to acquisition of multi-angle and multi-sensor satellite data.…”
Section: Campaign Overviewmentioning
confidence: 99%
“…Sobrino et al, 2008;Su et al, 2008;Timmermans, 2008b, c), the knowledge of bio-geophysical parameter retrieval from multi-parameter optical, thermal and microwave data and the ability of direct modeling of the underlying physical processes in forests and grassland remain challenging due to lack of appropriate observation data in humid climate. In EAGLE2006 an intensive filed campaign was conducted using different airborne instruments -an optical imaging sensor, an imaging microwave radiometer, and a flux airplane -for data acquisition and to collect extensive ground measurements simultaneously over one grassland site and two forest sites in addition to acquisition of multi-angle and multi-sensor satellite data.…”
Section: Campaign Overviewmentioning
confidence: 99%
“…However, due to the decrease in vegetation greenness during summer, increasing of the soil proportion, and decreasing of the emissivity values. Other emissivity values computed in previous works related to remote sensing experiences were used [35][36][37][38]. To estimate the downwelling atmospheric irradiance, the Ldown is measured in the 3.0-120.0 µm by the four-band net radiometer, although it is necessary to adapt it to the 8.0-14.0 µm thermal window to match with the thermal radiometer.…”
Section: In Situ Land Surface Temperaturementioning
confidence: 99%
“…Land surface temperature values are obtained with TES method (Gillespie et al, 1998) and these results are reported in (Sobrino et al, 2008). This heterogeneous agricultural area can be characterized from a thermodynamic point of view only with high resolution images.…”
Section: Land Surface Temperature Retrieved From Ahsmentioning
confidence: 99%
“…1). Various instruments were used to measure in the TIR domain, including multiband and single-band radiometers with a fixed field-of-view (Sobrino et al, 2008).…”
Section: Thermal Radiometric Field Campaignmentioning
confidence: 99%
See 1 more Smart Citation